2018
DOI: 10.1128/aem.02795-17
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress-Induced Loss of Iron Oxidoreduction Activities and Reacquisition of That Phenotype Depend on rus Operon Transcription in Acidithiobacillus ferridurans

Abstract: The type strain of the mineral-oxidizing acidophilic bacterium was grown in liquid medium containing elevated concentrations of sodium chloride with hydrogen as electron donor. While it became more tolerant to chloride, after about 1 year, the salt-stressed acidophile was found to have lost its ability to oxidize iron, though not sulfur or hydrogen. Detailed molecular examination revealed that this was due to an insertion sequence, IS, which belongs to the IS subgroup of the IS family, having been inserted dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…To evaluate the persistence and/or mobility of iMGEs and eMGEs in A. ferrooxidans strains under different growth conditions, we chose sublineage 2A strain CCM 4253 as a test case. In iron-oxidizing acidithiobacilli, changes in growth and stress conditions have proved to increase the transposition of IS elements at new sites, particularly in genes involved in iron oxidoreduction 36 38 . Thus, we performed genome resequencing of long-term iron- and sulfur-adapted cultures ( Experiment 1 , 20 generations).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the persistence and/or mobility of iMGEs and eMGEs in A. ferrooxidans strains under different growth conditions, we chose sublineage 2A strain CCM 4253 as a test case. In iron-oxidizing acidithiobacilli, changes in growth and stress conditions have proved to increase the transposition of IS elements at new sites, particularly in genes involved in iron oxidoreduction 36 38 . Thus, we performed genome resequencing of long-term iron- and sulfur-adapted cultures ( Experiment 1 , 20 generations).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the stress induced by elevated sodium chloride concentration caused ISAfd1 to be inserted downstream of the two promoters PI and PII of the rus operon (which encodes the iron oxidation pathway), thereby preventing its transcription. The ability to oxidize iron was restored after prolonged cultivation in the absence of sodium chloride, and two revertant strains were obtained 38 . Given the scarcity of genetic mutants of the taxon, we analyzed this mutation in further detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of the ability to anaerobically reduce Fe 3+ was also observed in At. ferridurans, which was caused by salt stress-induced insertional inactivation of the rus operon (Bonnefoy et al, 2018). This evidence pointed to the essential role of some gene(s) encoded by the rus operon in the mechanism of anaerobic respiratory Fe 3+ reduction in iron-oxidizing acidithiobacilli.…”
Section: Introductionmentioning
confidence: 89%
“…These reduced forms of sulfur are substrates for S. thermosulfidooxidans as it can oxidize not only iron but also sulfur compounds (Karavaiko et al, 2005). Several studies have reported that iron oxidation is more sensitive than sulfur oxidation to inhibitory effects by chloride and salt (Harahuc et al, 2000;Bonnefoy et al, 2018). Therefore, exposure to chloride possibly affects the preference for substrate utilization of S. thermosulfidooxidans, so that sulfur compounds may be preferred over Fe 2+ .…”
Section: Bioleaching Of Pyrite In the Presence Of Sodium Chloridementioning
confidence: 99%